2011
DOI: 10.21608/jssae.2011.55631
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Calcareous Soil Properties and Agriculture Methods for Achieving the Sustainable Agriculture Aspect

Abstract: The main objective of this investigation was to ameliorate calcareous soil properties, i.e., some hydrophysical and chemical properties of the sandy loam soil by using organic manure, i.e., composted rice straw at rate of 7.87 Mg f -1 +50%NPK and chicken manure at rate of 4.08 Mg f -1 +50%NPK as well as applying some agriculture methods, i.e., lines and prose for achieving the sustainable agriculture aspect. The field experiments were conducted in private farm of El Nubaria area, El-Behera Governorate, Egypt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Many investigators also showed that soil amendments greatly affected the physical and chemical properties of the soils and they could reduce the harmful effect of saline irrigation water (Fayed, 2009and Abou Hussien et al, 2009. El-Maghraby and Shaban (2011) found that, a slight decrease of soil pH values after wheat harvesting in the soil treated by organic fertilizers compared to untreated soil. This may be due to the soil buffering capacity.…”
Section: Introductionmentioning
confidence: 94%
“…Many investigators also showed that soil amendments greatly affected the physical and chemical properties of the soils and they could reduce the harmful effect of saline irrigation water (Fayed, 2009and Abou Hussien et al, 2009. El-Maghraby and Shaban (2011) found that, a slight decrease of soil pH values after wheat harvesting in the soil treated by organic fertilizers compared to untreated soil. This may be due to the soil buffering capacity.…”
Section: Introductionmentioning
confidence: 94%